Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Step-by-step explanation:
1) = Solution
(3x+2)(x-1) = 3x^2 - 3x+2x-2
= 3x^2 - x - 2
2) = (x-5)(2x+3)
= 2x^2 + 3x - 10x - 15
= 2x^2 - 7x - 15
3) = (2x+5)(3x-2)
= 6x^2 - 4x + 15x - 10
= 6x^2 + 11x - 10
(1)
=(3x+2)(x-1)
=3x(x-1)+2(x-1)
=3x^-3x+2x-2
=3x^-x-2
(2)
=(x-5) (2x+3)
=x(2x+3)-5(2x+3)
=2x^+3x-10x-15
=2x^-7x-15
(3)
=(2x+5) (3x-2)
=2x(3x-2)+5(3x-2)
=6x^-4x+15x-10
=6x^+11x-10
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.